2011
DOI: 10.1007/s00540-011-1239-8
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative infusion of dexmedetomidine at a high dose reduces postoperative analgesic requirements: a randomized control trial

Abstract: Among this small patient cohort, perioperative infusion of dexmedetomidine (1 μg/kg/h) resulted in antinociception without severe side effects. These results suggest that this method could be of interest with respect to improving postoperative pain status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…Dexmedetomidine is a potent sympatholytic agent, which can inhibit autonomic nervous system reactions such as increased heart rate and blood pressure following tracheal intubation and surgical stimuli; therefore, hemodynamic criteria may not be reliable for assessment of analgesic sufficiency. In addition, studies focusing on postoperative analgesic requirements after adjunctive DEX showed that the analgesic-sparing effect of DEX was confounded by its coexistent sedative and anxiolytic properties [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…Dexmedetomidine is a potent sympatholytic agent, which can inhibit autonomic nervous system reactions such as increased heart rate and blood pressure following tracheal intubation and surgical stimuli; therefore, hemodynamic criteria may not be reliable for assessment of analgesic sufficiency. In addition, studies focusing on postoperative analgesic requirements after adjunctive DEX showed that the analgesic-sparing effect of DEX was confounded by its coexistent sedative and anxiolytic properties [7,8].…”
Section: Introductionmentioning
confidence: 98%
“…Dexmedetomidine is an a 2 -adrenoreceptor agonist with sedative and antinociceptive effects in humans, mice, dogs and cats (Sabbe et al 1994;Slingsby & Taylor 2008;Ohtani et al 2011;Rangel et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This delayed analgesic request parallels the delay in patients receiving dexmedetomidine during general anesthesia. 28 It is important to emphasize that, although the level of sedation was measured in the operating room as well as in the PACU, in every case, the first analgesic demand occurred on the ward via PCA where the patient's level of sedation was not measured.…”
Section: Discussionmentioning
confidence: 99%